Karakterisasi Minyak Atsiri dari Simplisia Basah Ranting dan Daun sebagai Alternatif Subtitusi Kulit Batang Cinnamomum burmannii Blume - Budiarti, Mery; Jokopriambodo, Wahyu; Isnawati, Ani (Jurnal Kefarmasian Indonesia, 2018)
The bark of Cinnamomum burmannii Blume is the main raw material of Cinnamomum oil because its cinnamaldehyde content is higher than in the other parts. This condition lead to the exploitation of Cinnamomum burmannii Blume bark without any cultivation effort, thus it can cause the raw material scarcity. Twigs and leaves of Cinnamomum burmannii Blume are also known to contain cinnamaldehyde therefore it provide a potential alternative source of cinnamaldehyde. The purpose of this research is to investigate the characteristic of Cinnamomum burmannii Blume essential oil which includes refractive index, profiling of chemical constituent and percentage of cinnamaldehyde as a marker compound. This research used three fresh Cinnamomum burmannii Blume simplicia of bark, twigs and leaves from two selected growing locations: Tawangmangu and Purwokerto. Simple water distillation method was conducted, together with characterization and refractive index using refractometer, followed by qualitative and quantitative analysis with Thin Layer Chromatography (TLC) and Gas Chromatography (GC). The results showed Cinnamomum burmannii Blume oil derived from bark, twig and leaf have different profiles, but all have cinnamaldehyde as the main component. The leaf produces higher essential oil yield percentage compared to the twig with a cinnamaldehyde content that is comparable to the bark by 50% of cinnamaldehyde content in cinnamomum bark oil.